Training and development - Mathur Krishna Mohan
Training is a reciprocal process of teaching and learniing a body of knowledge, skills and techniques and the related methods of works. Training is an investment in human resources and is seen as a vehicle of change. Organisational climate has to be conducive to training and training to be effective and job oriented must get full support and attention of top management. On the job training can not be replaced by class room training because 80 to 90 percent of all development takes place on the job. Training and development therefore are complementary and mutually inter-dependent and are vital aspects of organisational success. Thus training is a continous ongoing process which involves the following steps
Keywords: Training; Police -- Training